Coexistence of lupus vulgaris with pure neuritic leprosy with incomplete claw hand - Angoori Gnaneshwar Rao (Wolters Kluwer Medknow Publications, 2016)
Coexistence of two chronic granulomatous diseases in an individual is rare. Here, we present coexistence of lupus vulgaris (LV) and pure neuritic leprosy with incomplete claw hand deformity in an 11-year-old immunocompetent girl, who presented with deformity and ulcer involving right upper limb. Characteristic clinical features and histopathology of biopsy from the ulcer assisted in establishing the diagnosis of LV and leprosy.